Protiobrabne lastnosti jekla 42CrMo4, nitriranega v nepulzirajoči in pulzirajoči plazmi - Podgornik, Bojan (Kovine zlitine tehnologije, 1999)
The tribological properties of plasma and pulse plasma nitrided 42CrMo4 steel were investigated and compared to hardened steel. Contact surfaces of the samples were characterized by metallographic, SEM microscopic, microhardness and profilometric techniques before and after wear testing. Wear tests were performed on a pin-on-disc wear testing machine in which nitrided pins were mated to hardened ball bearing steel discs under dry sliding conditions. The resulting wear loss as well as the coefficient of friction were monitored as a function of load, sliding speed and test time. Results show improvement of the tribological properties of 42CrMo4 steel after plasma and pulse plasma nitriding. Improvement becomes more evident when the testing conditions become more severe. It was also found that the compound layer should be removed from the nitrided surface to avoid impairment of the tribological properties by its fracture followed by the formation of hard abrasive particles.
Keywords: tribološke lastnosti; jeklo; nitriranje